ReacTickles: playful interaction with information communication technologies. (26th March 2009) - Keay-Bright, Wendy
This article presents a vision of information communication technologies (ICTs) as a playful trigger for relaxation and exploration, and investigates the benefits of this approach for young children with autism spectrum conditions. Playfulness in this context is considered for its repetitious, rhythmic and experiential value rather than as an intervention for the acquisition of skills; ICT is proposed as a medium for its physical and sensory affordances rather than as a task-focused application. To explain this notion, I describe how the ReacTickles software system, designed to harness the multisensory properties of ICTs, has increased the potential for unique and personal forms of interaction through the close coupling of physical input and digital output. To conclude, I discuss how adopting an interpretational approach enabled many of those who contributed to the design of ReacTickles to determine its context of use.